Cu2O thin films prepared by using four different copper salts at a low temperature: An investigation of their physical properties. (1st March 2020) - Altindemir, G.; Gumus, C.
Abstract: In this study, cuprous oxide (Cu2 O) films were prepared using four different copper salt ((CH3 COO)2 Cu·H2 O, CuSO4 ·5H2 O, Cu(NO3 )2 ·3H2 O, and CuCl2 ·2H2 O) with the SILAR method at a low temperature (60 °C) on a glass substrate with 40 immersion cycles. The structural, optical, morphological and electrical properties of the films were investigated. In the X-ray diffraction (XRD) analysis, it was found that Cu2 O thin films were polycrystalline, and there were no great differences between the structural properties of the films. The optical properties of the Cu2 O thin film were analyzed by absorption spectrum results. As the thickness value of the Cu2 O thin films increased, the energy band gap values decreased. In the FE-SEM (Field Emission-Scanning Electron Microscope) images, it was seen that spherical agglomeration generally occurred in the films, and, in some films, there were rod-structured particles in spherical form. In the Hall measurements, Cu2 O thin films were found to have p -type electrical conductivity, and the electrical resistivity values of the films ( ρ ) were found to be 1.24 × 10 4, 4.06 × 10 4, 2.86 × 10 3, and 1.67 × 10 4 Ωcm, respectively. The mobility values ( μ ) of the films were found to be 174, 87, 80, and 23 cm 2 /V, respectively.